2019
DOI: 10.7717/peerj.8046
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress as a potential target in acute kidney injury

Abstract: BackgroundAcute kidney injury (AKI) is a major problem for health systems being directly related to short and long-term morbidity and mortality. In the last years, the incidence of AKI has been increasing. AKI and chronic kidney disease (CKD) are closely interconnected, with a growing rate of CKD linked to repeated and severe episodes of AKI. AKI and CKD can occur also secondary to imbalanced oxidative stress (OS) reactions, inflammation, and apoptosis. The kidney is particularly sensitive to OS. OS is known a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 98 publications
1
41
0
Order By: Relevance
“…OS serves an important role in the occurrence and development of AKI ( 44 ). It has been demonstrated that OS is enhanced in LPS-induced models of AKI ( 45 ) and that the MAPK signaling pathway is an essential modulator of altered gene transcription in response to increased OS ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…OS serves an important role in the occurrence and development of AKI ( 44 ). It has been demonstrated that OS is enhanced in LPS-induced models of AKI ( 45 ) and that the MAPK signaling pathway is an essential modulator of altered gene transcription in response to increased OS ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both acute kidney injury (AKI) and chronic kidney disease (CKD) have been associated with decreased antioxidant defense and/or increased ROS that contribute to the disease progression [ 3 , 4 ]. AKI is defined as a sudden loss of renal function and CKD as decreased function, i.e., glomerular filtration rate (GFR) <60 mL/min/1.73 m 2 , or presence of kidney damage markers for more than 3 months [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The systemic toxicity of the metallic NPs can be diminished by targeting a specific site or by using biodegradable polymers as reduction and functionalizing agents. Metallic NPs may also show toxicity directly through their dissociated ions (24)(25)(26).…”
Section: Toxicity Of Npsmentioning
confidence: 99%
“…At higher concentration of ROS species, pro-inflammatory signalling pathways such as JNK and NF-κB cascade are activated. Higher ROS concentrations that cause prolonged OS lead to changes in the mitochondrial membrane potential causing cell death (25,(55)(56)(57)(58).…”
Section: Nanoparticles and Mitochondriamentioning
confidence: 99%